Boosting VO2max
Now, new research carried out at Odense University in Denmark demonstrates that some very simple, moderately intense training sessions will do the job. In the Danish study, eight cyclists rode their exercise cycles at an intensity of 80-90% V02max (88-95 per cent of maximal heart rate, 260-300 Watts) for 30 minutes per workout, three times per week. Eight other athletes performed interval workouts, which consisted of 10 seconds of all-out exertion at a stratospheric intensity of 880-1025 Watts, alternated with 50 seconds of rest. In the latter case, there were 20 work intervals per training session and three workouts per week.